2021
DOI: 10.1556/1326.2020.00762
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor chemical constituents of Toddalia asiatica (Linn) Lam root bark and its rational alternative medicinal parts by multivariate statistical analysis

Abstract: Abstract Toddalia asiatica (Linn) Lam (T. asiatica) as a traditional Miao medicine was investigated to find rational alternative medicinal parts for T. asiatica root bark and its antitumor chemical constituents by quantitative pharmacognostic microscopy, high performance liquid chromatography (HPLC) fingerprint and multivariate statistical analysis. A bivariate correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Bivariate analysis was used to establish a relationship between nineteen distinct peaks and the anti-tumor inhibition rate of different T. asiatica medicinal components, which was reflected in the form of peak correlation coefficients. Statistical investigations revealed that various compounds in T. asiatica exhibited anticancer activities, including toddalolactone, 4-methoxycinnamic acid, pimpinellin, isopimpinellin, and hesperidin appearing in that order (Luo et al, 2021).…”
Section: Antitumor Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivariate analysis was used to establish a relationship between nineteen distinct peaks and the anti-tumor inhibition rate of different T. asiatica medicinal components, which was reflected in the form of peak correlation coefficients. Statistical investigations revealed that various compounds in T. asiatica exhibited anticancer activities, including toddalolactone, 4-methoxycinnamic acid, pimpinellin, isopimpinellin, and hesperidin appearing in that order (Luo et al, 2021).…”
Section: Antitumor Effectsmentioning
confidence: 99%
“…Animal model experiments conducted in proving the hemostatic action of compounds isolated from the root bark of the plant T. asiatica was available in the literature, the considerable number of natural compounds such as furocoumarins isolated from T. asiatica plant root bark had been studied successfully by the considerable number of researchers (Luo et al, 2021;Ma et al, 2021). However, there is no scientific document available on comparative studies on pharmacologically active molecules that were isolated from the different active parts of the plant T. asiatica.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having anti-bacterial, anti-oxidant activities and other conventional pharmacological actions [1,2], hemostasis was its most significant pharmacological effect, had been applied and validated in thousands of years of Chinese folk history, which also led to derive its Chinese name Feilong Zhangxue or Jianxuefei [3][4][5]. Our research group earlier found the anti-inflammatory, analgesic, hemostatic and anti-tumor effects of T. asiatica which were experimentally verified [6][7][8], a large number of characteristic compounds including coumarins, alkaloids and flavonoids were isolated from ethyl acetate (EA) part, n-butanol (n-B) part in T. asiatica root bark which were also presumably deduced by high resolution mass spectrometry and chemical databases [9][10][11][12], most of these compounds were coumarins, more specifically furan coumarin. T. asiatica as a kind of natural medicines, it itself couldn't escape the congenital deficiency of these drugs which were rich in a variety of natural chemical compounds, diverse and complex pharmacological mechanisms to ultimately achieve the same therapeutical effect.…”
Section: Introductionmentioning
confidence: 99%